Do credit supply shocks have asymmetric effects? - David Finck; Paul Rudel (Empirical Economics, 2022)
They do. Partly. We identify credit supply shocks via sign restrictions in a Bayesian VAR and separate them into positive and negative. Using local projections, we find that positive credit supply shocks leave notably different prints in private debt, mortgage debt, and debt-to-GDP, as opposed to negative credit supply shocks. This pattern is caused by the response of household mortgage debt. Furthermore, we find evidence that positive credit supply shocks are the driving force behind boom-bust cycles. Yet, developments behind the boom-bust cycle cannot explain the strong and persistent response in debt; but house prices tend to. However, if we abstract from potential asymmetries, we get rather mild results, which underestimate the true effects of credit supply shocks.
Keywords: C11; E21; E22; E32; 330; Credit supply shocks; Household debt; Asymmetry; Local projections